KEANEKARAGAMAN MAMALIA BESAR BERDASARKAN KETINGGIAN TEMPAT DI TAMAN NASIONAL GUNUNG CIREMAI - Gunawan, Gunawan; Kartono, Agus Priyono; Maryanto, Ibnu (JURNAL BIOLOGI INDONESIA, 2008)
ABSTRACTMammalian Diversity Based on Altitudinal Range at Gunung Ciremai NationalPark. Gunung Ciremai was declared as national park in 2004. As a new national park,the mammalian data is lacking especially about mammalian diversity based on vegetationcomposition and altitudinal in Gunung Ciremai. The observation was conducted in 4habitats, such as: pine forest, lowland forest, mountain forest and subalpine forest elevationfrom 500 to 3078 m asl. Number of species found are 9 (7 species was through directobservation and 2 specis by indirect observation). Species richness index is 1,04; speciesdiversity index is 1,00 and species evennes index is 0,52. Relationship between mammaliandiversity and vegetation composition, that is sapling density, poles density and tree densityshowing significant value just for sapling density (r2= 0,501 dan p= 0,044). Relationshipbetween mammalian diversity and altitudinal show significant value (r2= 0,881 and P=0,025).Key words: mammalian diversity, habitat, vegetation composition and altitudinal